A stable iodine-doped multi-walled carbon nanotube-polypyrrole composite with improved electrical property. (30th October 2015) - Fan, Li-na; Xu, Xue-cheng
Abstract: A highly conductive carbon nanotubes-polymer composite is fabricated by iodine doping. Interestingly, the conductivity of both multi-walled carbon nanotubes (MWCNTs) and polypyrrole (PPy) keeps unaffected by iodine, but the MWCNT-PPy composite shows ∼3.4 times higher conductivity only with 5 wt% of iodine doped the composite. The electrical property is proved to be stable at room temperature. Hall Effect tests reveals the increasing carrier concentration and mobility of doped MWCNT-PPy lead to the high conductivity. According to Raman and XPS investigation, PPy and MWCNTs form an extended conjugated system through π–π interactions, which favors the p–π interactions of iodine with MWCNT-PPy. As a result, a typical conductive carrier N + in MWCNT-PPy composite raises significantly. Besides, the carrier mobility also increases due to the higher conjugate degree. Our results suggest that iodine doping is a useful way to improve the conductivity of as prepared CNTs-conjugated polymer products.